In vitro antimicrobial evaluation between the selected anti-diabetic medicinal plant seeds in Sri Lanka - Gowri Rajkumar; Mihiri Rangika Jayasinghe; Vinotha Sanmugarajah (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: The management of Diabetes mellitus is a major contest for clinicians in nowadays. Uncontrolled hyperglycaemia increases the risk of numerous complications in the body. Although a number of antidiabetic drugs are available for therapeutic intervention, herbal management for diabetes is encouraged due to its low side effects and effectiveness, throughout the world. This current in-vitro study is a comparative evaluation of antimicrobial activities of four selected anti-diabetic medicinal plant seeds namely Syzygium cumini (L.) Skeels, Sinapis alba L., Trigonella foenum-graecum L. and Nigella sativa L. which are commonly found in Jaffna District, Sri Lanka. Materials and method: Crude ethanol extract of seeds was investigated for their antibacterial activity against three bacterial strains as Enterococcus faecalis, Staphylococcus aureus and Escherichia coli by using agar well diffusion method in three replicates. The statistical analysis was carried out using one-way Analysis of variance. Results: The seeds extract of S. cumini showed maximum zone of inhibitions (24.70, 16.147, 10.37 mm) and S. alba represented minimum zone of inhibitions (1.08, 1.08, 0 mm) against all three types of human pathogens (E. faecalis, S. aureus and E. coli) respectively. Results showed that significant amount of inhibition zone was obtained against all the selected bacterial species which were comparable with positive control streptomycin. Conclusion: The chances of discovering antimicrobial activities in seeds of S.cumini extract is the highest and it is proposed that the plants which presented significant antimicrobial activities should be tested in detail to reveal their potential as probable antibiotics against particular pathogens. Therefore, this current research process demonstrates the S.cumini seeds can be used for developing nutraceutical products and long-term storage herbal drugs for the treatment of infectious diseases as well as diabetes in future.